(untitled) (Research, Society and Development, 2020)
The objective of this work is to analyze the experience of a remote education modality in the city of Caicó, state of Rio Grande do Norte, EJA em Ação, in the exceptional social distance caused by the Covid-19 pandemic. With the need for social isolation, the school community is challenged to provide a “continuity” of the teacher and student relationship in other non-school spaces. As a comparative exercise, historical experience in the 1960s will be taken, the installation of the Emissora de Educação Rural, with the implantation of the Basic Education Movement - MEB and the use of radio as a mediating element of teaching-learning. It was through radio waves that information about health, evangelization and education reached the homes of a large part of the population of Caico. The vestiges of this memory, of an education through the radio, is one of the guiding threads of the reinterpretation of radio schools in the current times. The applied methodology will take place through the analysis of the discussion of “memory places” by Pierre Nora, the radio as a mediator and pedagogical tool in teaching and the analysis of publications in the media about the EJA in Action Project, carrying out a comparative exercise between the temporalities of the Basic Education Movement - MEB and the EJA in Action Project in the city of Caicó. Keywords: MEB; Memory; Radio; Education; EJA project in Action; Caicó